Primary Choledocholithiasis 15 Years Postcholecystectomy - Michael Simon; Irfan Nazir Hassan; Dhanasekaran Ramasamy; David Wilson (Case Reports in Medicine)
Gallstone disease is extremely prevalent in the western society with laparoscopic cholecystectomy (LC) being the standard treatment for patients with symptomatic gallstones. The prevalence of common bile duct (CBD) stones with concomitant gallstones increases with age from 8–15% in patients <60 years of age and up to 60% in the elderly. There have been only a few case reports of postcholecystectomy bile duct stones occurring more than 10 years following surgery in the literature. Most of these reports describe the presence of stones within the gallbladder/cystic duct remnant or secondary to migrating surgical clips.